Glofitamab in Relapsed/Refractory Mantle Cell Lymphoma: Results From a Phase I/II Study - Phillips, Tycel Jovelle; Carlo-Stella, Carmelo; Morschhauser, Franck; Bachy, Emmanuel; Crump, Michael; Trněný, Marek; Bartlett, Nancy L; Zaucha, Jan; Wrobel, Tomasz; Offner, Fritz; Humphrey, Kathryn; Relf, James; et al. (Journal of clinical oncology, 2025)
PURPOSE: Patients with relapsed/refractory (R/R) mantle cell lymphoma (MCL) have a poor prognosis. The phase I/II NP30179 study (ClinicalTrials.gov identifier: NCT03075696) evaluated glofitamab monotherapy in patients with R/R B-cell lymphomas, with obinutuzumab pretreatment (Gpt) to mitigate the risk of cytokine release syndrome (CRS) with glofitamab. We present data for patients with R/R MCL. METHODS: Eligible patients with R/R MCL (at least one previous therapy) received Gpt (1,000 or 2,000 mg) 7 days before the first glofitamab dose (single dose or split over 2 days if required). Glofitamab step-up dosing was administered once a day on days 8 (2.5 mg) and 15 (10 mg) of cycle 1, with a target dose of 16 or 30 mg once every 3 weeks from cycle 2 day 1 onward, for 12 cycles. Efficacy end points included investigator-assessed complete response (CR) rate, overall response rate (ORR), and duration of CR. RESULTS: Of 61 enrolled patients, 60 were evaluable for safety and efficacy. Patients had received a median of two previous therapies (range, 1-5). CR rate and ORR were 78.3% (95% CI, 65.8 to 87.9) and 85.0% (95% CI, 73.4 to 92.9), respectively. In patients who had received previous treatment with a Bruton tyrosine kinase inhibitor (n = 31), CR rate was 71.0% (95% CI, 52.0 to 85.8) and ORR was 74.2% (95% CI, 55.4 to 88.1). CRS after glofitamab administration occurred in 70.0% of patients, with a lower incidence in the 2,000 mg (63.6% [grade ≥2, 22.7%]) versus 1,000 mg (87.5%; grade ≥2, 62.5%) Gpt cohort. Four adverse events led to glofitamab withdrawal (all infections). CONCLUSION: Fixed-duration glofitamab induced high CR rates in heavily pretreated patients with R/R MCL; the safety profile was manageable with appropriate support.
Keywords: lidé; Middle Aged; Adult; lokální recidiva nádoru; Female; Antibodies, Monoclonal, Humanized; Antibodies, Bispecific; Humans; Cytokine Release Syndrome; lidé středního věku; mužské pohlaví; protilátky bispecifické; ženské pohlaví; syndrom uvolnění cytokinů; Aged, 80 and over; Lymphoma, Mantle-Cell; senioři nad 80 let; Male; Aged; humanizované monoklonální protilátky; dospělí; Neoplasm Recurrence, Local; lymfom z plášťových buněk; senioři